2021
DOI: 10.3390/land10090907
|View full text |Cite
|
Sign up to set email alerts
|

Linking Morphological Spatial Pattern Analysis and Circuit Theory to Identify Ecological Security Pattern in the Loess Plateau: Taking Shuozhou City as an Example

Abstract: Located in an ecologically fragile area in China’s eastern part of the Loess Plateau, Shuozhou City has faced environmental challenges imposed by frequent urban expansion and mining activities in recent years. As ecological security patterns (ESP) identification and optimization are significant to regional biodiversity and ecosystem services, this study combined morphological spatial pattern analysis (MSPA) and circuit theory to construct and optimize regional ESP. Results show the number and area of ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It not only sustains landscape ecological processes, but also contributes to the enrichment of local regional biodiversity (Li, 2020). With low resistance to expansion, it is a channel between two adjacent ecological source sites and an important flow channel for species migration in the region (Yang et al, 2021). This study identified the ecological corridors by using MCR and the gravity model (Fig.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It not only sustains landscape ecological processes, but also contributes to the enrichment of local regional biodiversity (Li, 2020). With low resistance to expansion, it is a channel between two adjacent ecological source sites and an important flow channel for species migration in the region (Yang et al, 2021). This study identified the ecological corridors by using MCR and the gravity model (Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…As shown in Table 2, this study selected seven factors that represent natural and human aspects as the ecological resistance factors for constructing a comprehensive resistance surface evaluation index system for ecological expansion (Li, 2020; Yang et al, 2021; Qin et al, 2023). The seven factors are all closely related to ecological resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Slope information of the study area was extracted from elevation data, and the Euclidean distance from the residential area, water area, and road was calculated by the distance calculation tool. Based on the actual situation in the study area and concerning existing studies, the resistance level of each landscape factor was classified into five levels ( Ding et al., 2021 ; Yang et al., 2021 ). We assigned weights to each factor based on the entropy weighting method ( Ji et al., 2020 ), and used the raster calculator in ArcGIS software, to overlay and obtain a resistance raster for the study area.…”
Section: Methodsmentioning
confidence: 99%
“…In the ecological corridor extraction, the minimum cumulative resistance model (MCR) is the traditional method which can determine the direction and optimal route of biological flow, but cannot clarify the spatial extent and key nodes of ecological corridors (Huang et al, 2019;Dai et al, 2021). The application of circuit theory effectively bridges this gap by simulating the direction of bio-flow through the random walk of electric current and determining the key locations in the corridor according to the magnitude of current intensity (Peng et al, 2018b;Yang et al, 2021;Yu et al, 2021) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%